2021
DOI: 10.1088/1755-1315/761/1/012004
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Bio and Mineral Fertilizers on Growth and Yield of Wheat (Triticum estivum L.)

Abstract: A field experiment was conducted at the college of Agriculture – university of Anbar during the winter season of 2018-2019 using complete randomized blocks design (RCBD) to investigate effects of bio-fertilizer (BF) and different rates of mineral fertilizers (MF) from fertilizer recommendation (FR) on the growth and yield of wheat (IBAA cultivar). The growth and yield traits consisted of plant height (PLH), number of tillers (NT), number of spike (NS), number of grains per spike (NGPS), weight of 1000 grains (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The yields and components of quinoa plants increased with increasing soil application of compost in comparison with those without application (Fawy et al, 2017). Kadhum et al (2021) suggested that the used of bio-fertilizer and mineral fertilizer have an active role in supplying the plant with the necessary nutrients and thus increasing the growth indicators of the plant like weight of grains due to the regularity work of plant hormones when the availability of nutrients K, P and N, which increased the division of cells and increased the number of branch tillers carrying flowering and fertile spikes. The increased vegetative growth of the plant also improves the exploitation of active rays of photosynthesis, especially at the beginning of growth season, which increases the availability of the anabolized substances in support of the emergence plant.…”
Section: Bio-fertilizers and Compost Fertilizations Combined With Or ...mentioning
confidence: 96%
See 1 more Smart Citation
“…The yields and components of quinoa plants increased with increasing soil application of compost in comparison with those without application (Fawy et al, 2017). Kadhum et al (2021) suggested that the used of bio-fertilizer and mineral fertilizer have an active role in supplying the plant with the necessary nutrients and thus increasing the growth indicators of the plant like weight of grains due to the regularity work of plant hormones when the availability of nutrients K, P and N, which increased the division of cells and increased the number of branch tillers carrying flowering and fertile spikes. The increased vegetative growth of the plant also improves the exploitation of active rays of photosynthesis, especially at the beginning of growth season, which increases the availability of the anabolized substances in support of the emergence plant.…”
Section: Bio-fertilizers and Compost Fertilizations Combined With Or ...mentioning
confidence: 96%
“…The increased vegetative growth of the plant also improves the exploitation of active rays of photosynthesis, especially at the beginning of growth season, which increases the availability of the anabolized substances in support of the emergence plant. Thus, 50% of the mineral fertilizer can be substituted with the biological fertilizer to reduce the risk of contamination and reduce the cost of mineral fertilizer (Kadhum et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The results of [5] showed that the combination of rhizobium inoculum isolated from the bean plant with 50% mineral fertilization was superior in the number of root nodes and the highest weight of the root nodes, as well as the yield increased significantly by 109.4% compared to the comparison treatment. The success of the biological fertilizer used as an inoculate added to the plant growth medium depends on the efficiency of the host organism, the ability of the organisms added to coexist with the host plant, and whether they can compete with the organisms present in the root zone in the soil [6,7]. Microorganisms also differ in their nature, behavior, and activity and the type of nutrients that these organisms provide to the plant [8].…”
Section: Introductionmentioning
confidence: 99%